Quercetin relieves coronary atherosclerosis via regulating fibroblast growth factor 2: Quercetin relieves coronary atherosclerosis - Shi, Rui; Liu, Zhaozheng; Yin, Jinzhu; Deng, Yue (Cellular and Molecular Biology, 2023)
This study aims to investigate the role of quercetin in coronary atherosclerosis and explore its possible mechanisms. Hematoxylin-eosin (H&E), immunohistochemical (IHC), and aniline blue staining were used to analyze the pathological changes in the cross-section of the aorta. Traditional Chinese Medicine Systems Pharmacology Database (TCMSP), Swiss Target Prediction, and PubChem were utilized to predict and screen the bioactive ingredients of traditional Chinese medicine (Huanglian, Yuxingcao, and Jinyinhua) for coronary atherosclerosis. Inflammatory factors and vascular protection parameters were quantitatively detected using ELISA and western blot. The proliferation and migration of vascular smooth muscle cells (VSMC) were evaluated using the Cell Counting Kit-8 (CCK-8), 5-ethynyl-2-deoxyuridine (EdU), and wound healing assays. The targets of quercetin were predicted using DisGeNET, Matascape, SWISSMODEL, cellular thermal shift assay (CETSA), and fluorescence titrimetric methods. Based on our findings, quercetin was identified as the active component of Huanglian, Yuxingcao, and Jinyinhua that exerted a positive effect on coronary atherosclerosis. In vivo and in vitro data demonstrated that quercetin improved the pathological changes in model mice and inhibited the proliferation, migration, and inflammatory response of VSMC cells. Specifically, we found that fibroblast growth factor 2 (FGF2) is a direct target of quercetin, and overexpression of FGF2 attenuated the anti-atherosclerosis function of quercetin. Overall, our study confirms the functional role of the quercetin-FGF2 axis in the progression of coronary atherosclerosis, providing a potential target for its treatment.